Consumptive use and Water Requirement of Dwarf Wheat in Light Textured Soils of Rajasthan - Jain, T C; Jain, K C (Annals of Arid Zone, 2016)
Two year studies on consumptive use of wheat (Kalyan Sona) in light textured soils of Rajasthan indicated that over 6U percent of water consumed by the crop was obtained from the upper 30 cm soil layer and less than 40 per cent from 30-60 em depth. The consumption below 60 cm soil depth was very little only during the later part of the season' Applying 40 to 50 mm water after a cumulative pan evaporation of 45-55 mm from standard V.S Pan evaporimeter was found optimum. The total number of irrigation thus required were 8 to 10 with a total depth of 360 to 450 mm.